Celso O. Espejo Philippine rondalla master - Guadalupe, Jocelyn Timbol (2012)
The purpose of the study was to document the teaching methodology of Celso O. Espejo as demonstrated on two contrasting rondalla groups, the first consisting of children and the second, consisting of adults. Data gathered from observing the teaching demonstrations and four interviews with Celso Espejo revealed prominent features of Espejo's philosophy and pedagogy. These are: 1) Training in tremolo technique with a wide range of dynamic levels, 2) Use of the down pick technique to begin playing melodies and counter-melodies, 3) Mastery of a particular technique(s) required for study and performance of a specific repertoire, 4) Use of a visual tool which he calls "chart notation" to develop pre-reading and aural learning competencies applicable to reading standard music notation. Underlying all these strategies is Espejo's insistence on the presence of the entire group even if a certain section is being focused during rehearsal. Espejo, in the interviews freely shared his vision and perspectives on the Philippine rondalla. The prominent pedagogical strategies and views are discussed in the context of the aesthetic philosophy, cognitive theories and psychological studies in music education.
Keywords: Rondalla -- Study and teaching; Music education; Instrumental music